A distinctive new species of the coral shrimp genus Microprosthema Stimpson, 1860 from the Atlantic coast of Florida and Honduras (Decapoda: Stenopodidea: Spongicolidae) - Anker, Arthur; Joseph W. Goy (Zootaxa, 2023)
A new species of the spongicolid coral shrimp genus Microprosthema Stimpson, 1860 is described on the basis of three specimens collected by hand while scuba diving off the Atlantic coast of southern Florida, with additional photographic records from Roatan, Honduras. Microprosthema dimitrisorum sp. nov. can be separated from all presently known species of the genus by a unique combination of morphological characters, and most easily, by its highly diagnostic and conspicuous colour pattern consisting of large red spots on most of the body and appendages.